Analysis of Recycled HDPE Composite with OPEFB-Based Cellulose Fiber Reinforcement Characteristics for Casing Electronic Materials - Zulnazri; Rozanna Dewi; Novi Sylvia; Agam Muarif; Syaiful Maliki; Ahmad Fikri (LPPM Universitas Malikussaleh, 2022)
Composite is a product of advanced material innovation which has better mechanical properties than a single material. In addition, composites also have high impact strength so they can be applied as cassing electronic, construction of boat walls, car dashboards, and others. This innovative product can be made from high density polyethylene (HDPE) thermoplastic waste material with cellulose filler based empty palm oil fruit bunches (OPEFB). In this study, a comparison of composite modifications between HDPE and cellulose fibers was carried out. The ratio of matrix and filler composition used in this study is 90:10. The mixing of HDPE : Cellulose fibers using injection melt blending system and extruder technique. The composites are then made into specimens for tensile strenght and impact tests. The results of the tensile strenght and impact test HDPE : Cellulose fiber composite with ratio 90:10 is 27.000 Mpa and 0.261750877 Joules. Analysis results Scanning Electron Microscopy (SEM) on the morphology of the composite fracture, it is known that there is a bond between the matrix (HDPE) and filler (cellulose fiber). The results of this study indicate that composite of HDPE: cellulose fiber based OPEFB (90:10) has potential as a material for cassing electronic.